PERLINDUNGAN HUKUM TERHADAP TAYANGAN INFOTAIMENT YANG BERHUBUNGAN DENGAN SIARAN TV DAN ANAK - Irda, Elisabet; Michael, Tomy (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
Infotaiment shows have an impact that cannot be separated from the influence of the mass media. The influence can be in the form of behavior, fashion and even attitudes towards certain ideologies. It all depends on how prepared humans are to deal with television information. If what is shown is a good achievement achieved by a celebrity, this can be used as a lesson for his fans. But if what is shown is behavior that violates immoral norms, it is certainly not good. Ironically, infotainment shows more emphasis on the lifestyle of celebrities, starting from minimal clothing, hairstyles and social interactions, which in fact they adopt more of a western lifestyle. This has a very dangerous impact if it is continuously shown to the public, especially to children who are easy to follow things that are often seen by children. The rise of television shows with soap operas and reality shows is in dire need of infotainment, and vice versa where infotainment is an inseparable part of television shows.